GAYA KEPEMIMPINAN KEPALA SEKOLAH PEREMPUAN DI SEKOLAH DASAR NEGERI SE-KECAMATAN SEPAUK KABUPATEN SINTANG - Marsiana Marsiana; Luhur Wicaksono; Rini Fatmasari (STKIP Persada Khatulistiwa Sintang, 2023)
Women's leadership is still a debated issue today, especially considering that leadership is in a central position in an institution. Therefore, this study aims to analyze the Leadership Style of Female Principals in Public Elementary Schools in Sepauk District, Sintang Regency. This research uses a qualitative descriptive design, with the type of research that is phenomenological qualitative research. The primary research data sources came from informants, namely school principals, teachers, and staff from SDN 01 Sepauk, SDN 02 Lengkenat, SDN 27 Gernis, Sepauk District, Sintang District. Data collection techniques are interviews, observation, and documentation. Test the data's validity using credibility, transferability, dependability, and confirmability tests. Data analysis using data reduction, data presentation, and conclusion. Based on the research and data analysis, this study concluded that the three school principals, namely the Principal of SDN 01 Sepauk, the Principal of SDN 02 Lengkenat, and the Principal of SDN 27 Gernis, had fulfilled their roles as leaders, innovators, and motivators. The principal of the school has a democratic leadership style. This is shown by the fact that the Principal always involves other parties to be involved in determining the final decision of a meeting held or related to making a decision.